2020
DOI: 10.1136/jech-2019-213523
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of alcohol misuse: mediation and interaction by school performance in a Swedish birth cohort

Abstract: BackgroundChildren whose parents misuse alcohol have increased risks of own alcohol misuse in adulthood. Though most attain lower school marks, some still perform well in school, which could be an indicator of resilience with protective potential against negative health outcomes. Accordingly, the aim of this study was to examine the processes of mediation and interaction by school performance regarding the intergenerational transmission of alcohol misuse.MethodsData were drawn from a prospective Swedish cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…This study showed that, consistent with many previous findings ( 25 , 29 39 , 46 , 48 50 , 62 ), risky parental health behaviors have a significant risk of being transmitted to their children. It is usually easy for children to imitate their parents' behaviors even if they are negative or unhealthy ( 25 28 , 63 , 64 ), and, therefore, parents' words and deeds are very important in preventing risky health behaviors in children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed that, consistent with many previous findings ( 25 , 29 39 , 46 , 48 50 , 62 ), risky parental health behaviors have a significant risk of being transmitted to their children. It is usually easy for children to imitate their parents' behaviors even if they are negative or unhealthy ( 25 28 , 63 , 64 ), and, therefore, parents' words and deeds are very important in preventing risky health behaviors in children.…”
Section: Discussionsupporting
confidence: 91%
“…According to Cockerham's Health Lifestyle Theory ( 45 ), high-SES parents not only avoid the transmission of their own negative health behaviors but also their gentle parenting style helps to develop self-control in their children ( 45 ). In contrast, low-SES families tend to adopt strict, punitive, and authoritarian parenting styles, leading to children's poor self-control and making them more likely to emulate their parents' risky health behavior ( 28 31 , 33 , 34 , 39 , 46 52 ). In other words, the intergenerational transmission of risky health behaviors is likely to be in reverse to the SES gradient.…”
Section: Introductionmentioning
confidence: 99%
“…52–53; Nordlie, 2003 ; Orford et al, 2013 ). Participants also reported feeling disconnected emotionally: problems at school or sick leave from work were reported, and alcohol misuse problems in adulthood, which has also been reported previously (Almquist, Bishop, Gustafsson & Berg, 2020 ; Marino et al, 2018 ; Rospenda et al, 2010 ).…”
Section: Discussionsupporting
confidence: 77%
“…Children’s beliefs regarding positive or negative effects of alcohol are influenced by watching parental drinking, can develop in a short period of time, and can serve as predictors of their current and future drinking behaviours 23. Parental alcohol use or misuse is associated with subsequent alcohol consumption and misuse in adolescence through adulthood 456. Yet, many studies and discussions of adolescent drinking have failed to include parental drinking even as a confounding variable in the analyses, let alone as a major explanatory factor 7.…”
mentioning
confidence: 99%